2023
DOI: 10.1115/1.4062124
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing a Ceramic Turbine Rotor for a Compact Jet Engine

Abstract: Compact military-grade jet engines offer many potential applications, including use in remotely piloted vehicles, but can be expensive to use for research and development purposes. A study aimed at increasing the power and thrust output of an inexpensive commercial compact engine found a material limitation issue in the turbomachinery. To gain the additional power, hotter turbine inlet temperatures were required. This temperature increase exceeded the limit of current uncooled metal turbine rotors but could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…[195][196][197][198][199] Fine feature resolution (in the range of ∼10-20 μm) is an advantage but limitations in composition (mainly oxides) and/or part thickness (<∼10 mm) are current challenges with commercially available feedstock. 200 Despite these limitations, it remains the most advanced in terms of commercial equipment and ceramic feedstock (3DCeram, Admatec, Lithoz, and Tethon 3D) and ability to make complex shapes (e.g. inner channels) with fine feature size.…”
Section: Review Of Additive Manufacturing Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…[195][196][197][198][199] Fine feature resolution (in the range of ∼10-20 μm) is an advantage but limitations in composition (mainly oxides) and/or part thickness (<∼10 mm) are current challenges with commercially available feedstock. 200 Despite these limitations, it remains the most advanced in terms of commercial equipment and ceramic feedstock (3DCeram, Admatec, Lithoz, and Tethon 3D) and ability to make complex shapes (e.g. inner channels) with fine feature size.…”
Section: Review Of Additive Manufacturing Technologymentioning
confidence: 99%
“…One direction in the field utilizes preceramic polymers to improve the issues with low solids content and/or RI of powders, but is limited to feature sizes (∼<1 mm) due to off‐gassing and shrinkage during the cure and pyrolysis steps, respectively 195–199 . Fine feature resolution (in the range of ∼10–20 μm) is an advantage but limitations in composition (mainly oxides) and/or part thickness (<∼10 mm) are current challenges with commercially available feedstock 200 . Despite these limitations, it remains the most advanced in terms of commercial equipment and ceramic feedstock (3DCeram, Admatec, Lithoz, and Tethon 3D) and ability to make complex shapes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A vertical line at 22.6 μm indicates the estimate of critical flaw size (c), which is the maximum allowable flaw size for a given stress, for alumina. 35 It is found using Equation 3, where the K Ic is the fracture toughness, and σ f is the material's modulus of rupture, as reported in ref. 35 .…”
Section: Cuboid and Cylinder Delaminatingmentioning
confidence: 99%
“…However, even with the greater geometric flexibility that AM affords, porosity and cracking during curing or pyrolysis remain a major obstacle to the creation of bulk ceramic components using preceramic polymers. 5,[8][9][10] The use of filler materials in preceramic polymers can aid in reducing the shrinkage, porosity, and cracking in polymer-derived ceramic composites by providing a rigid framework for the composite during curing and pyrolysis and by providing faster diffusion pathways for the evolved gas species to escape. 2, 12 For example, with a DLP technology, O'Masta et al found that the use of 10 vol.% mullite in a polysiloxane increased the thickness of a part that could be printed without cracking from 1 to <3 mm 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in using preceramic polymers as feedstocks in additive manufacturing (AM) technologies, in part because several AM technologies are already well‐suited to using thermoset resins—in particular stereolithography (SLA), 7 digital light processing (DLP), 8,9 and material extrusion AM 5,10,11 —and in part because ceramic materials are typically challenging to form into complex shapes, a major strength of AM. However, even with the greater geometric flexibility that AM affords, porosity and cracking during curing or pyrolysis remain a major obstacle to the creation of bulk ceramic components using preceramic polymers 5,8–10 …”
Section: Introductionmentioning
confidence: 99%